(untitled) (mathematica didactica, 2021)
To provide adaptive support for students, is a challenging task in mathematical modelling processes. Pre-service teachers’ adaptive intervention competence in mathematical modelling processes is to be facilitated in the teaching-and-learning-laboratory-seminar in Koblenz. For an intervention adapted to the difficulties of the students, various authors emphasize the requirement of a precise diagnosis. In this study, this hypothesis is empirically studied with the help of a quantitative testing instrument. The influence of a correct diagnosis is investigated before and after attending the teaching-and-learning-laboratory-seminar.